Integrasi Best Worst Method dan MOORA dalam Sistem Pendukung Keputusan Orientasi Karir Siswa SMK - Suma, Nur Alim M.; Hadjaratie, Lillyan; Pakaya, Nikmasari; Padiku, Indhitya R. (Universitas Negeri Gorontalo, 2026)
The career orientation process in vocational high schools was frequently constrained by student confusion and teacher subjectivity due to the absence of analytical guidelines. This study developed a decision support system to provide objective career recommendations. The main contribution of this research was the provision of an early-stage analytical guideline based on mathematical computation for students. The system development utilized the Waterfall method. For computation, the Best Worst Method (BWM) was used to calculate criteria weights based on expert preferences, which was combined with Multi-Objective Optimization on the basis of Ratio Analysis (MOORA) to rank alternatives. The computation results of the BWM vector successfully achieved a consistency ratio of 0.0468. The confusion matrix testing on 30 samples indicated an accuracy rate of 86.67% and the System Usability Scale (SUS) evaluation obtained a score of 72.2 (Acceptable). However, this study is limited by the small sample size and implementation scope within a single school. These findings indicate that the integration of BWM and MOORA can be used as an initial analytical guideline to support career guidance services in vocational high schools. Proses penentuan orientasi karir di SMK sering terkendala kebingungan siswa dan subjektivitas guru akibat ketiadaan pedoman analitis. Penelitian ini mengembangkan sistem pendukung keputusan untuk memberikan rekomendasi karir secara objektif. Kontribusi utama penelitian ini adalah penyediaan pedoman analitis awal berbasis komputasi matematis bagi siswa. Pengembangan sistem menggunakan metode Waterfall. Untuk komputasi, metode Best Worst Method (BWM) digunakan untuk menghitung bobot kriteria berdasarkan preferensi pakar, yang dipadukan dengan Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) untuk merangking alternatif. Hasil komputasi vektor BWM sukses mencapai rasio konsistensi 0,0468. Pengujian confusion matrix pada 30 sampel menunjukkan tingkat akurasi 86,67% dan evaluasi System Usability Scale (SUS) memperoleh skor 72,2 (Acceptable). Meskipun demikian, penelitian ini memiliki keterbatasan pada ukuran sampel yang kecil dan cakupan implementasi yang masih terbatas di satu sekolah. Temuan ini menunjukkan bahwa integrasi BWM dan MOORA dapat digunakan sebagai pedoman analitis awal dalam mendukung layanan bimbingan karir di SMK.